Prevalence of three-rooted mandibular permanent first and second molars in the Saudi population - Abdullah Mahmoud Riyahi; Khalid Alssum; Hassan Hadadi; Abdulaziz Alsayyari; Terki Alebrah; Fahd Aljarbou (Elsevier, 2019)
Introduction: This study aims to explore the frequency and factors affecting the prevalence of an extra root in the lower first and second permanent molars in the Saudi population. Methods: Images of 379 Saudi patients who underwent CBCT for routine dental treatment were assessed. The CBCT images were evaluated on a 34-inch LED screen in a dark room and assessed by two examiners to count the prevalence of an additional root in the lower molars. Laterality and the gender factors were used to analyze that prevalence. Percentages represent categorical variables; Fisher's exact test and Chi square test were also used for the categorical variables. Results: In the lower first molars, the prevalence of extra root in female patients was 5.7%, 3% in male patients and the overall prevalence was 3.05%; in lower second molars, the prevalence was 1.81% in female patients and 3.04% in male patients with an overall prevalence of 1.48%. A statistically significant difference was fond in the existence of an additional root with regard to laterality, to be more common on the right compared to the left side for both mandibular molars. The extra root prevalence was statistically significant in female patients at the first molar compared to male patients (p < 0.05). Conclusion: The overall of extra roots prevalence in the lower first and second molars in the Saudi population are 3.05% and 1.48%, respectively. Consideration and identification of this variation is essential to ensure successful endodontic treatment. Keywords: Three-rooted lower molars, Extra root, Radix entomolaris, Radix paramolaris, Saudi population